2020
DOI: 10.1093/jxb/eraa085
|View full text |Cite
|
Sign up to set email alerts
|

ETHYLENE RESPONSE FACTOR39–MYB8 complex regulates low-temperature-induced lignification of loquat fruit

Abstract: Flesh lignification is a specific chilling response that causes deterioration in the quality of stored red-fleshed loquat fruit (Eribotrya japonica) and is one aspect of wider chilling injury. APETALA2/ETHLENE RESPONSIVE FACTOR (AP2/ERF) transcription factors are important regulators of plant low-temperature responses and lignin biosynthesis. In this study, the expression and action of 27 AP2/ERF genes from the red-fleshed loquat cultivar ‘Luoyangqing’ were investigated in order to identify transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 78 publications
(126 reference statements)
0
41
0
Order By: Relevance
“…BT2, BTB domain contained protein; KFBs, Kelch Domain F-Box proteins; MdMIEL, MYB30-INTERACTING E3 LIGASE 1 in apple; OsFBK1, F-box protein containing Kelch 1 in rice; OsGRF8, GROWTH REGULATING FACTOR 8 in rice; OsUCL23, uclacyanin family in rice; PA, proanthocyanidins; PtoUBC34, E2 ubiquitin-conjugating enzyme 34 in Populus tomentosa; SPL, SQUAMOSA PROMOTER BINDING PROTEIN-LIKE. (Zhang et al, 2020c). OsMYB30 binds to and activates the promoters of Os4CL3 and Os4CL5, and brings about the accumulation of G and S lignin in rice (Li et al, 2020e).…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…BT2, BTB domain contained protein; KFBs, Kelch Domain F-Box proteins; MdMIEL, MYB30-INTERACTING E3 LIGASE 1 in apple; OsFBK1, F-box protein containing Kelch 1 in rice; OsGRF8, GROWTH REGULATING FACTOR 8 in rice; OsUCL23, uclacyanin family in rice; PA, proanthocyanidins; PtoUBC34, E2 ubiquitin-conjugating enzyme 34 in Populus tomentosa; SPL, SQUAMOSA PROMOTER BINDING PROTEIN-LIKE. (Zhang et al, 2020c). OsMYB30 binds to and activates the promoters of Os4CL3 and Os4CL5, and brings about the accumulation of G and S lignin in rice (Li et al, 2020e).…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…Previous studies have demonstrated that EjAP2-1 works in coordination with EjMYB1 and EjMYB2 for transcriptional regulation of Ej4CL1 ( Zeng et al, 2015 ). Zhang et al (2020) recently found that the EjERF39 and EjMYB8 protein complex activates Ej4CL1 by protein-DNA interaction with the promoter of Ej4CL1 . Furthermore, utilization of the loquat transcriptome has allowed for the discovery of more lignification-related transcription factors ( Lin et al, 2018 ; Liu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, ectopic expression of MYB ( Xu et al, 2014b ; Wang et al, 2016 ), NAC (NAM, ATAF1, ATAF2, and CUC2; Ge et al, 2017 ), APETALA2/Ethylene Response Factor (AP2/ERF; Zeng et al, 2015 ; Zhang et al, 2020 ), Heat Shock Factor (HSF; Zeng et al, 2016 ), and Homobox from Arabidopsis thaliana (HAT; Xu et al, 2019b ) family members in loquat flesh resulted in changes in the expression of phenylpropanoid pathway genes. For example, the transcripts of Ej4CL1 can be induced by EjERF39 and EjHSF1 or repressed by EjAP2-1 and EjbHLH1, resulting in changes in the lignin content ( Zeng et al, 2015 , 2016 ; Xu et al, 2019b ; Zhang et al, 2020 ). EjNAC3 and EjHAT1 can modify the expression of EjCAD -like and EjCAD5 , respectively ( Ge et al, 2017 ; Xu et al, 2019b ).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, whether and how the expression of StInvInh2 is regulated by cold-responsive regulators is not clear. Interestingly, the StInvInh2 promoter contains a dehydration-responsive element/C-repeat (DRE/CRT) motif, which is generally bound by APETALA2/ethylene-responsive factor (AP2/ERF) TFs 19 , 20 . Therefore, cold-responsive AP2/ERFs could be considered candidate regulators of StInvInh2 transcription in cold-stored potato tubers.…”
Section: Introductionmentioning
confidence: 99%